2023
DOI: 10.1002/ppul.26695
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory monitoring with a wireless and nonadhesive belt measuring diaphragm activity in preterm and term infants: A multicenter non‐inferiority study

Anouk W. J. Scholten,
Zhuozhao Zhan,
Hendrik J. Niemarkt
et al.

Abstract: IntroductionWe determined if the heart rate (HR) monitoring performance of a wireless and nonadhesive belt is non‐inferior compared to standard electrocardiography (ECG). Secondary objective was to explore the belt's respiratory rate (RR) monitoring performance compared to chest impedance (CI).MethodIn this multicenter non‐inferiority trial, preterm and term infants were simultaneously monitored with the belt and conventional ECG/CI for 24 h. HR monitoring performance was estimated with the HR difference and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…In our opinion, a swift replacement of the belt to correct the position would have prevented these adverse events. Indeed, in our 24 h feasibility and monitoring study, no adverse skin events were reported [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our opinion, a swift replacement of the belt to correct the position would have prevented these adverse events. Indeed, in our 24 h feasibility and monitoring study, no adverse skin events were reported [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was approved by the Ethical Board of the Máxima Medical Centre (NL77561.015.21) and registered in the Netherlands Trial Register (NL 9478). This study was performed in addition to a multicenter monitor performance study of the Bambi Belt (NL9480) [ 16 ]. This study was monitored by an independent body (Clinical Trial Centre Maastricht).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation